Citation‐Capture Rates for Economics Journals: Do they Differ from Other Disciplines and Does it Matter?. Issue 1 (10th December 2015) - Anderson, David L.; Tressler, John
Abstract : This paper compares the rate of citation‐capture across the social sciences, sciences, business school disciplines and economics. It also explores differences in the rate of citation‐capture between leading journals in economics and a representative science category, and between higher and lower ranked economics journals. Short‐term citation counting as used in impact factors and journal ranking schemes is shown to favour sciences over social sciences. In addition, within economics, short‐term impact factors are systematically biased towards lower ranked journals. Our results imply that the use of leading multidisciplinary journal rankings as a proxy for direct citations introduces an unreported bias in research assessment. Such biases are in addition to those attributable to the well‐known differences in the total number of cites received by papers across various disciplines.